VD_FINDINFO HC / 2015 / 399 vom 31. März 2015 - VD Tribunal cantonal (2015)
DEMEURE DU CRÉANCIER, CONTRAT INDIVIDUEL DE TRAVAIL, DÉLAI DE RÉSILIATION, TORT MORAL, DOMMAGES-INTÉRÊTS | 324 al. 1 CO, 324 CO, 49 CO